Diagnostic Performance of Colposcopy in Detecting High-Grade Cervical Lesions among HPV DNA-Positive Women in Tertiary Care Centre of Nepal - Gurung, Sarita Rana; Acharya, Bijaya Chandra; Subedi, Hem Nath; Kaduwal, Shankar; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2025)
Background: Cervical cancer remains a significant public health concern, particularly in low- and middle-income countries. Colposcopy is a vital diagnostic modality for detecting cervical intraepithelial neoplasia (CIN) in women testing positive for high-risk human papillomavirus (HPV). However, its diagnostic accuracy for identifying high-grade lesions (CIN II and above) warrants further evaluation. This study aimed to assess the diagnostic performance of colposcopy among HPV DNA–positive women and correlate its findings with histopathology. Methods: A hospital-based cross-sectional study was conducted among 93 HPV DNA–positive women undergoing colposcopic evaluation at a tertiary care centre. Histopathological examination was used as the gold standard. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of colposcopy were calculated. Associations between colposcopic findings and sociodemographic or clinical variables were analyzed using Chi-square or Fisher’s Exact tests. Results: Colposcopy showed a sensitivity of 83.3%, specificity of 63.6%, PPV of 71.4%, NPV of 77.8%, and a diagnostic accuracy of 73.3%. Statistically significant associations were found between colposcopic findings and age (p = 0.016), participation in cervical screening programs (p = 0.022), and history of postcoital bleeding (p = 0.045). A fair correlation (χ2=23.34, p<0.001) was observed between colposcopy and histopathology findings. Conclusion: Colposcopy demonstrates moderate diagnostic accuracy in identifying high-grade cervical lesions among HPV-positive women. While it remains an essential component of cervical cancer screening and management, its performance can vary based on patient age and screening history. Integration with cytology and histopathological confirmation improves diagnostic precision. Strengthening colposcopy training and referral systems is crucial for enhancing reliability and reducing false interpretations.